2004
DOI: 10.1177/0256090920040203
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Service Quality: Servqual vs. Servperf Scales

Abstract: Quality has come to be recognized as a strategic tool for attaining operational efficiency and improved business performance. This is true for both the goods and services sectors. However, the problem with management of service quality in service firms is that quality is not easily identifiable and measurable due to inherent characteristics of services which make them different from goods. Various definitions of the term ‘service quality’ have been proposed in the past and, based on different definitions, diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
264
0
37

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(306 citation statements)
references
References 50 publications
5
264
0
37
Order By: Relevance
“…However, some authors 1,21 found the SERVPERF scale to outperform the SERVQUAL scale in terms of both reliability and validity. But SERVQUAL has more and diverse applicability.…”
Section: Theoretical Observations Service Qualitymentioning
confidence: 99%
“…However, some authors 1,21 found the SERVPERF scale to outperform the SERVQUAL scale in terms of both reliability and validity. But SERVQUAL has more and diverse applicability.…”
Section: Theoretical Observations Service Qualitymentioning
confidence: 99%
“…While perception is definable and measurable because it represents consumers' experiences about a particular service, expectations are subjected to multiple interpretations, as noted in several studies (e.g. Jain & Gupta, 2004;Dabholkar et al, 2000;Brown, Churchill, & Peter, 1993). This can cause the tool to have poor reliability.…”
Section: Servqual Modelmentioning
confidence: 99%
“…Jain and Gupta's (2004) results are clear that SERVPREF is superior: they recommend that it be employed for assessing overall service quality and when making service quality comparisons. For management interventions, SERVQUAL, however, remains better diagnostically.…”
Section: The Servqual Instrument and Is Service Qualitymentioning
confidence: 99%